Survival of Common Eider Somateria mollissima adult females and ducklings during brood rearing - Flint, Paul L; Moran, Christine L; Schamber, Jason L (Wildfowl, 1998)
We studied survival of adult female and duckling Common Eiders during brood rearing at two sties o the Yukon-Kuskokwim Delta, Alaska, in 1997. Duckling survival to 30 days of age was 19% 10% (95% CI). Seventy-three percent of radio-marked adult females had lost all their ducklings by 30 days after hatch. Duckling survival was not related to hatch date. We estimate an average of 0.84 ducklings fledged per adult female radio-marked at hatch. Most broods moved to salt water within 15 days of hatch. Adult female survival during the first 30 days of brood rearing was 96 6% (95% CI). Mortality of adult females during brood rearing is probably higher than during other times of the year.